Exploring the causal factor effects of hypothyroidism on ischemic stroke: a two-sample Mendelian randomization study - Tian, Yi; Shi, Xiao Qin; Shui, Jing Wen; Liu, Xiao Yu; Bu, Ya; Liu, Yi; Yin, Li Ping (Frontiers in Neurology, 2024)
Background: Observational studies have suggested a possible association between hypothyroidism and increased risk of ischemic stroke. However, a causal relationship remains unclear.Methods: Data on single nucleotide polymorphisms (SNP) associated with hypothyroidism and ischemic stroke were sourced from the FinnGens database and the UK Biobank of European descent.Both databases underwent separate two-sample Mendelian randomization (MR) analyses. A subsequent meta-analysis of MR results using a random-effects model was conducted to determine the causal relationship between hypothyroidism and ischemic stroke. Results: All five analyses indicated a positive causal relationship between hypothyroidism and ischemic stroke. MR analysis of the association between hypothyroidism and ischemic stroke yielded a result of the inverse variance weighted (IVW) method at 4.7411[1.3598-16.5308], p=0.0146. The analysis of ischemic stroke (without excluding controls) yielded a result of the IVW method of 4.5713[1.3570-15.3986], p=0.0142. MR analysis with cerebral infarction yielded a result of the IVW method at 1.0110[1.0006-1.0215], p=0.0373. The MR analysis with cerebrovascular disease sequelae yielded an IVW method result of 2.4556 [1.0291-5.8595], p=0.0429. Analysis for the sequelae of cerebrovascular disease (without excluding controls) yielded an IVW method result of 2.4217 [1.0217-5.7402], p=0.0446. No evidence of heterogeneity or horizontal pleiotropy was found. The meta-analysis of the five MR results was 2.24 [1.18~4.26], p=0.025.Our two-sample Mendelian randomization study suggested a causal relationship between hypothyroidism and ischemic stroke, indicating that hypothyroidism could be a risk factor for ischemic stroke. However, further studies are required to elucidate the underlying biological mechanisms.